2014
DOI: 10.1242/jcs.148148
|View full text |Cite
|
Sign up to set email alerts
|

β-adrenergic receptor signaling regulates Ptgs2 by driving circadian gene expression in osteoblasts

Abstract: The sympathetic nervous system modulates bone remodeling and mediates the expression of core clock genes in part through the badrenergic receptor (b-AR) in osteoblasts. In this study, we show that in MC3T3-E1 osteoblastic cells that isoproterenol (Iso), a nonselective b-AR agonist, upregulated the transcriptional factor Nfil3, and induced rhythmic mRNA expression of prostaglandinendoperoxide synthase 2 (Ptgs2, also known as Cox2). The rhythmic effects of Iso on Ptgs2 expression were mediated by interplay betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…This result suggests that regulation via the E-box site generates the oscillation in the Ptgs2 transcription. In addition to its regulation via E-box, Ptgs2 transcription is regulated by Nfil3 via the D-box site (22) and Rev-erb␣ via RORE, as we have described in the present study. The amplitude and phase in the rhythmic expression of Ptgs2 may be balanced by these regulations.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This result suggests that regulation via the E-box site generates the oscillation in the Ptgs2 transcription. In addition to its regulation via E-box, Ptgs2 transcription is regulated by Nfil3 via the D-box site (22) and Rev-erb␣ via RORE, as we have described in the present study. The amplitude and phase in the rhythmic expression of Ptgs2 may be balanced by these regulations.…”
Section: Discussionsupporting
confidence: 64%
“…Bmal1 control of Ptgs2 transcription has been suggested in other tissues (7,22,25,38). Moreover, our previous data obtained from a DNA microarray in UESCs isolated from day 4.5 of rat pregnancy (49) suggested that the expression level of the Ptgs2 transcript is rhythmic.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…When cells reached confluency, medium supplemented with 10 mM β-glycerophosphate and 10 mg/ml ascorbic acid was used. Media were changed every 2-4 days (Hirai et al, 2014a).…”
Section: Bone Histomorphometrymentioning
confidence: 99%